BELLBOYS' VERBAL AND NON-VERBAL COMMUNICATION STRATEGIES IN ENHANCING GUEST SERVICE EXPERIENCE DURING CHECK-IN AND CHECK-OUT PROCESSES AT GRAND MIRAGE RESORT - Dewa Dharma Santika; Made Suardana (Undiksha Press, 2026)
Communication plays a vital role in the hospitality industry, particularly in ensuring service quality and maintaining guest satisfaction. Bellboys, as frontline employees, interact directly with guests during the check-in and check-out processes, making effective communication an essential aspect of service delivery. This study aims to identify, describe, and analyze the verbal and non-verbal communication strategies used by bellboys in enhancing guest service experiences at Grand Mirage Resort. A descriptive qualitative method was employed, with data collected through observations, interviews, and documentation. The findings reveal that verbal communication is primarily used to greet guests, provide information, confirm requests, offer assistance, and maintain smooth interactions throughout the service process. In addition, non-verbal communication, including eye contact, facial expressions, body posture, gestures, and professional appearance, plays a significant role in conveying friendliness, politeness, confidence, and professionalism. The integration of verbal and non-verbal communication contributes positively to guest satisfaction and the overall service experience. However, the study also identifies several challenges, including inconsistencies in communication practices and limited awareness of the importance of non-verbal cues among some bellboys. Therefore, regular communication training and continuous professional development are recommended to strengthen communication competencies and further improve service quality in the hospitality industry.